PENGARUH PENGETAHUAN PERPAJAKAN, SOSIALISASI, SANKSI DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI DEPOK TOWN SQUARE - Maulana, Ivandi; Farina, Khoirina (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2025)
This study aims to analyze the factors that influence the compliance of MSME taxpayers at Depok Town Square. The analysis method used in this research is Partial Least Squares (PLS) with the help of SmartPLS software. The research sample consisted of 96 respondents who were MSME actors. The variables studied include tax knowledge, tax sanctions, tax socialization, and service quality from the tax authority. Data were collected through distributing questionnaires to respondents. The results of the analysis show that the four variables have a significant effect on MSME taxpayer compliance. These findings provide important insights for tax authorities in formulating appropriate policies and strategies to increase the level of tax compliance, especially in the MSME sector.Keywords: Tax Knowledge; Tax Sanctions;Tax Socialization; Taxpayer Compliance